A two-dimensional model of an electromagnetic accelerator - Hamola, Orest; Hamola, Marta (Publishing House of Lviv Polytechnic National University, 2012)
The mathematical model of an accelerator’s magnetic field, which takes into account its symmetry, the nonlinearity of an armature characteristic B(H), and eddy currents, has been investigated. The model has been developed on the basis of the finite elements method. The armature that moves under the applied Ampere’s force has been represented as a movable distribution of magnetic permeance. Розглянуто математичну модель магнітного поля прискорювача, що враховує його симетрію, нелінійність характеристики B(H) арматури, вихрові струми. Модель створено на базі методу скінченних елементів. Арматуру, що рухається під дією сили Ампера, змодельовано як рухомий розподіл магнітної проникності.
Двовимірна модель електромагнітного прискороювача
Keywords: coil; eddy currents; electromagnetic accelerator; ferromagnetic core (armature)